STRUGGLE AS SEEN IN ANDRZEJ SAPKOWSKI S THE WITCHER (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this research is to reveal the struggle of Geralt to find his adopted daughter and obstacles of his journey The writer uses qualitative methods using two data sources namely primary data and secondary data The main data source is the novel of the main character then the secondary data source is books articles and reference journals on the internet about the novel Into The Witcher and in analyzing it the writer uses an objective approach that focuses on external and internal elements The results show that the main character Geralt s struggle to be accepted in human society he acknowledge the flaws and shortcomings of humans but he also recognizes that they are worth protecting personal relationship with his lover Yennefer Geralt and Yennefer s relationship is portrayed as tumultuous and difficult witch both characters struggling to understand each other and their own feelings fighting his enemies Geralt s struggle as he faces off his enemies the fight show just how difficult it is for geralt to overcome his enemies and emerge victorious and finding adopted daughter Geralt s determination to find Ciri and the sense of resposibility he feel for her Despite the challenges he face he is committed to doing whatever it takes to locate her and keep her safe < p>
Keywords: Geralt, Relationship, struggles, obstacles, human society, The Witcher.